HUBUNGAN KONDISI KESEHATAN FISIK, FUNGSI KOGNITIF, DAN TINGKAT STRESS DENGAN KEMANDIRIAN LANSIA DI MEDAN SUMATERA UTARA - Siregar, Rinco; Blessery (Yayasan Nuraini Ibrahim Mandiri, 2024)
As the elderly population grows, there will be a greater need to support their daily activities, since aging can lead to a decline in physical abilities and independence. This study aimed to determine the relationship among physical health, cognitive function, stress levels, and independence of elderly people in Medan Marelan. It was a descriptive study with a cross-sectional approach, involving 92 elderly participants who met certain criteria. This study used Perceived Stress Scale (PSS), Mini Mental State Examination (MMSE), vital signs measurements (blood pressure, stethoscope, thermometer, stopwatch), and the Barthel Index (IB) measurements. The results showed that physical health (p = 0.002), cognitive function (p = 0.026), and stress levels (p = 0.000) were significantly associated with the level of independence of elderly in performing daily activities. The study recommends that public health centers in North Sumatra should provide interventions to improve the health, cognitive function, and stress levels of elderly.